Synthesis and Crystal Structure of Terephthalaldehyde-bis-(thiosemicarbazone)-bis-(dimethyl sulfoxide) Solvate - Su, Wei; Li, Peiyuan; Liu, Lifeng; Chen, Rui; Huo, Lini (Asian Journal of Chemistry, 2012)
A thiosemicarbazone single crystal synthesized with a formula as C10H12N6S2·2C2H6OS, was synthesized by 1,4-phthalaldehyde and 4-methylthiosemicarbazide. The crystal is triclinic, space group P-1 with unit cell parameters: a = 5.9519(5) Å, b = 7.4721(7) Å, c = 12.5450(13), a = 77.348(8)º, b = 78.672(8)º, g = 79.193(7)º, V = 527.64(8) Å3, Z = 1, Mr = 436.63, Dc = 1.374 g/cm3, μ = 0.471 mm-1, F(000) = 230, R = 0.0844, wR = 0.2607 for 1902 reflections with I > 2s (I).